2015
DOI: 10.5897/jdoh2014.0138
|View full text |Cite
|
Sign up to set email alerts
|

Perfection of unused Ni-Ti endodontic files, myth or reality? A scanning electron microscope (SEM) study

Abstract: Endodontic rotary files have been developed to improve the quality of root canal preparation. However, such instruments have a risk of separation. In most cases, the files are not checked for quality before use. Instead, they are often removed from the packages, sterilized and used without being examined for the presence of imperfections or debris. Practitioners were always to be blamed of such mishaps, but recently there has been some investigations claiming that these files are not flawless and far from perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Mechanism of such consequences are still not argumented with sufficient evidences and requires more detailed and targeted researches. Some studies reported that amount of surface impurities may be associated with prevalence of surface defects presented in various forms over working part of endodontic files [6,11,13,15]. Combination of both surface defects and surface impurities may affect file's condition in significant manner during its clinical usage and potentially compromise its functional prognosis over repetitive mode of action.…”
Section: Kalyoncuoğlu Et Al Demonstrated That No Significantmentioning
confidence: 99%
See 1 more Smart Citation
“…Mechanism of such consequences are still not argumented with sufficient evidences and requires more detailed and targeted researches. Some studies reported that amount of surface impurities may be associated with prevalence of surface defects presented in various forms over working part of endodontic files [6,11,13,15]. Combination of both surface defects and surface impurities may affect file's condition in significant manner during its clinical usage and potentially compromise its functional prognosis over repetitive mode of action.…”
Section: Kalyoncuoğlu Et Al Demonstrated That No Significantmentioning
confidence: 99%
“…Scanning electron microscopy (SEM) combined with energy dispersive spectrometry (EDS) have been widely used as non-destructive methods in number of *Address correspondence to this author at the National Healthcare University of Ukraine, All-Ukrainian Association of Endodontists, Kyiv, Ukraine; E-mail: bban@i.ua studies provided for the assessment of endodontic files' surface [6,7,9]. Based on the obtained outcomes it was concluded that even new endodontic instruments may demonstrate various surface defects, most of which were related with the specific process of their manufacturing and packaging [6,[11][12][13][14]. On the other hand SEM-EDS approach also helped to revealed that counterfeit endodontic rotary instruments characterized with increased number of different surface defects, while also with prominent SEM-differences compared to original design of the file [7].…”
Section: Introductionmentioning
confidence: 99%